Variación temporal de la familia Mymaridae (Hymenoptera) en la Reserva de la Biosfera Sierra de Manantlan, Jalisco, México. - Hernández Vázquez, Salvador (Instituto de Ecología, A.C., 1998)
Populations of mymarid were monitored weekiy for one year using yellow sticky card traps, at Las Joyas Scientific Station (LJSS) and the community of Corralitos in the Sierra de Manantlán Biosphere Reserve, Jalisco, México. The mymarid were collected on populations of Zea diploperennis at the LJSS and on dry-land corn fields in Corralitos. The greatest increase of the mymarid population in Zea diploperennis ocurred from July to september and in December, while in corn they appeared during the period of July to September.